DAMPAK PEMANFAATAN TEKNOLOGI INFORMASI DALAM BIDANG PEMASARAN TERHADAP PENDAPATAN UMKM BUTIK KHOMITA SUMBAWA BESAR - Isro Zaskia Zain; Ika Fitriyani; Elly Karmeli (Jurnal Ekonomi & Bisnis, 2023)
This research aims to determine differences of MSMEs income levels in Sumbawa Besar before and after the use of information technology in the marketing sector (e-commerce). This study was conducted at the Khomita Boutique, Sumbawa Besar. The type of data used in this study was quantitative data in the form of income data before and after the use of information technology in the marketing sector (e-commerce) obtained through the financial report of the Khomita Boutique, Sumbawa Besar. The data was analysis in this study used the mean difference test technique, including the paired samples statistics test, paired samples correlations test, and paired samples t-test. The results of this study showed that there are differences in the income levels of the Khomita Boutique, Sumbawa Besar before and after the use of information technology in the marketing sector (e-commerce). The mean income received by the Khomita Boutique, Sumbawa Besar after the use of information technology in the marketing sector (e-commerce) was greater than the income received in the previous period. Thus, it can be concluded that the use of information technology in the marketing sector (e-commerce) has a positive impact on increasing income at the Khomita Boutique, Sumbawa Besar.